Can AI Diagnose Rare Diseases? Shortening the Diagnostic Odyssey - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Can AI Diagnose Rare Diseases? Shortening the Diagnostic Odyssey The journey to a rare disease diagnosis is often described as a "diagnostic odyssey"—a ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine